2015
DOI: 10.1590/2359-3997000000016
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated fracture healing with teriparatide

Abstract: O n December 2, 2013, it was called our attention that the case report (1) contained few paragraphs that bear a likeness to a further review (2). This occurred inadvertently when we entrusted the literature and a draft of this review (2) to others co-authors. Although we were not aware of theses similarities between the case report and this review. We nevertheless take full responsibility for this error.The primary objective of our case report (1) is to describe a accelerated fracture healing with teriparatide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…PTH promotes early chondrogenesis and also osteogenesis in fracture models, which may have favorable implications for treatment of DNFs. Indeed, several case reports suggest PTH(1‐34) may promote healing of DNFs . A non‐placebo‐controlled trial of elderly osteoporotic women with pelvic factures showed an increased rate of radiographic healing and some clinical improvements in those treated with PTH(1‐84) .…”
Section: Agents and Biological Pathways That Promote Fracture Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…PTH promotes early chondrogenesis and also osteogenesis in fracture models, which may have favorable implications for treatment of DNFs. Indeed, several case reports suggest PTH(1‐34) may promote healing of DNFs . A non‐placebo‐controlled trial of elderly osteoporotic women with pelvic factures showed an increased rate of radiographic healing and some clinical improvements in those treated with PTH(1‐84) .…”
Section: Agents and Biological Pathways That Promote Fracture Healingmentioning
confidence: 99%
“…Indeed, several case reports suggest PTH(1-34) may promote healing of DNFs. [68][69][70] A non-placebo-controlled trial of elderly osteoporotic women with pelvic factures showed an increased rate of radiographic healing and some clinical improvements in those treated with PTH(1-84). 71 A placebocontrolled trial of PTH in patients with closed distal radius fractures failed to achieve its primary endpoint, but accelerated radiographic healing was observed at the lower dose tested.…”
mentioning
confidence: 99%
“…In human clinical trials, teriparatide administration has shown to accelerate callus formation and lessen the risk of nonunion, and improve fracture healing [14][15][16] . Theoretically, the positive impact of teriparatide in early callus formation and fracture healing is important for an early return of functional outcomes and for preventing late complications.…”
Section: Introductionmentioning
confidence: 99%